Biomechanical measures of clinician-defined unsteadiness during a forward stepdown task in individuals post-arthroscopy for femoroacetabular impingement syndrome. (March 2022) - Jochimsen, K.N.; Brown-Taylor, L.; Perry, J.; Glaws, K.; Lewis, C.L.; Ryan, J.; Di Stasi, S.
Abstract: Background: Patients with femoroacetabular impingement syndrome can present with aberrant movement patterns including unsteady balance. Balance training is included in rehabilitation after hip arthroscopy and may improve quality of movement; however, specific biomechanical measures associated with clinician-defined balance impairments are unknown. We aimed to understand these associations as they may inform targeted rehabilitative interventions. Methods: The forward stepdown is a clinical test used to evaluate movement quality, including balance. 23 individuals at least one-year post-arthroscopy for femoroacetabular impingement syndrome and 15 healthy comparisons performed the forward stepdown, recorded by 3-dimensional motion capture and 2-dimensional video. Three physical therapists graded the 2-dimensional video for steadiness. Two-way analyses of variance were used to evaluate the interaction of group (post-arthroscopy/healthy comparison) by steadiness (steady/unsteady), for center of pressure medial-lateral excursion, center of pressure path length, and lateral trunk, pelvis, and lower extremity joint excursions. Findings: Six (26.1%) participants post-arthroscopy and five (33.3%) healthy comparisons were categorized as unsteady. The odds of being categorized as unsteady were not greater for participants post-arthroscopy ( P = 0.72). There were no significant interactions; however, participants with clinician-defined unsteady balance, regardless of group, had significantly greater frontal plane trunk excursion, greater hip excursion, and greater center of pressure path length than those with steady balance ( P ≤ 0.006). Interpretation: The odds of being categorized as unsteady were not greater for individuals post-arthroscopy for femoroacetabular impingement syndrome. Clinician-defined unsteadiness was associated with greater frontal plane trunk and hip motion which may be rehabilitation targets to improve balance during a dynamic single-leg task. Highlights: Unsteady balance during a forward stepdown presented in 26.1% of individuals post- arthroscopy. Unsteady balance during a forward stepdown presented in 33.3% of healthy comparisons. The odds of being unsteady were not greater for individuals post-hip arthroscopy. Clinician-defined unsteadiness was associated with greater frontal plane trunk and hip motion.